Detecção de Paracoccidioides sp. em amostras ambientais aerossóis - Arantes, Thales Domingos [UNESP] (2012)
Taking into account that paracoccidioidomycosis infection occurs by inhalation of the asexual conidia produced by Paracoccidioides sp. in its saprobic phase, this work presents the collection of aerosol samples as an option for environmental detection of this pathogen, by positioning a cyclonic air sampler at the entrance of armadillo burrows. Detection strategies included: direct culture, extinction technique culture and Nested PCR of the ITS1-5.8S-ITS2 region, as well as the evaluation of one armadillo (D. novemcinctus) as positive control for the studied area. Although the pathogen could not be isolated by the culturing strategies, the aerosol sampling associated with molecular detection by Nested PCR proved the best method for detecting Paracoccidioides sp. in the environment. Most of the ITS sequences obtained herein presented high similarity with the homologous sequences of P. lutzii from GenBank database, suggesting that this Paracoccidioides species may be not exclusive to mid-western Brazil as proposed so far